Plastic in Water and Its Implications in Human and Biological Systems - Sarkingobir, Yusuf; Tukur, Ummu (Bumi Publikasi Nusantara, 2025)
The objective of this work is to explain the harms of plastics present in water as they affect humans and relations. Plastics are major polymers in contemporary dealings of human endeavors. They are synthesized through the addition or condensation of monomer units and serve humans with their distinguishing benefits such as the ability to be processed to various things by molding. Extensive uses of plastics show that all human activities use plastic for one purpose or the other. Water utilized by humans is in constant contact with plastics indicating a probable pollution that affects human health. This paper reviews the role of water in the body (systems), types of plastics, types of plastics, harm to animals, concerned behaviors of plastics, harmful contents, and management. There is a need for enlightenment, and strict laws (policies).